The Character Values of The Pati Ka Offering Ritual at Kelimutu Lake - Maria Marietta Bali Larasati; Jhosephina Nirma Rupa (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2023)
This study aimed at describing the character value of education through understanding the semiotic meaning of the offerings ritual Pati Ka in the Kelimutu Lake. This study used descriptive qualitative and ethnolinguistic approach. The research subject were two people namely Mosalaki (clan chief) who organized the Pati Ka ritual and a local villager. Data collection techniques which is done by observation, interview and documentation. The techniques used in analyzing the data was the techniques model by Miles and Huberman with 4 stages namely, data collection, the data reduction, data analysis, data display and drawing conclusion. The result showed that the presence of the value of education, religious character, honest, hard work, spirit of nationality, love of country, communicative, love peace, environmental care, social care and responsibility through understanding the semiotic meaning of the offerings Pati Ka in Kelimutu Lake. Understanding the semiotic meaning of the offerings ritual Pati Ka has two dimensions of interlocking character value of education that is contained in the offerings ritual Pati Ka and that the meaning of the offerings itself.